Xenon modulates synaptic transmission to rat hippocampal CA3 neurons at both pre‐ and postsynaptic sites. (8th November 2019) - Nonaka, Kiku; Kotani, Naoki; Akaike, Hironari; Shin, Min‐Chul; Yamaga, Toshitaka; Nagami, Hideaki; Akaike, Norio
Abstract : Key points: Xenon (Xe) non‐competitively inhibited whole‐cell excitatory glutamatergic current ( I Glu ) and whole‐cell currents gated by ionotropic glutamate receptors ( I AMPA, I KA, I NMDA ), but had no effect on inhibitory GABAergic whole‐cell current ( I GABA ). Xe decreased only the frequency of glutamatergic spontaneous and miniature excitatory postsynaptic currents and GABAergic spontaneous inhibitory postsynaptic currents without changing the amplitude or decay times of these synaptic responses. Xe decreased the amplitude of both the action potential‐evoked excitatory and the action potential‐evoked inhibitory postsynaptic currents (eEPSCs and eIPSCs, respectively) via a presynaptic inhibition in transmitter release. We conclude that the main site of action of Xe is presynaptic in both excitatory and inhibitory synapses, and that the Xe inhibition is much greater for eEPSCs than for eIPSCs. Abstract: To clarify how xenon (Xe) modulates excitatory and inhibitory whole‐cell and synaptic responses, we conducted an electrophysiological experiment using the 'synapse bouton preparation' dissociated mechanically from the rat hippocampal CA3 region. This technique can evaluate pure single‐ or multi‐synapse responses and enabled us to accurately quantify how Xe influences pre‐ and postsynaptic aspects of synaptic transmission. Xe inhibited whole‐cell glutamatergic current ( I Glu ) and whole‐cell currents gated by the three subtypes of glutamate receptor ( I AMPA, I KA and I NMDA ). Inhibition of these ionotropic currents occurred in a concentration‐dependent, non‐competitive and voltage‐independent manner. Xe markedly depressed the slow steady current component of I AMPA almost without altering the fast phasic I AMPA component non‐desensitized by cyclothiazide. It decreased current frequency without affecting the amplitude and current kinetics of glutamatergic spontaneous excitatory postsynaptic currents and miniature excitatory postsynaptic currents. It decreased the amplitude, increasing the failure rate (Rf) and paired‐pulse rate (PPR) without altering the current kinetics of glutamatergic action potential‐evoked excitatory postsynaptic currents. Thus, Xe has a clear presynaptic effect on excitatory synaptic transmission. Xe did not alter the GABA‐induced whole‐cell current ( I GABA ). It decreased the frequency of GABAergic spontaneous inhibitory postsynaptic currents without changing the amplitude and current kinetics. It decreased the amplitude and increased the PPR and Rf of the GABAergic action potential‐evoked inhibitory postsynaptic currents without altering the current kinetics. Thus, Xe acts exclusively at presynaptic sites at the GABAergic synapse. In conclusion, our data indicate that a presynaptic decrease of excitatory transmission is likely to be the major mechanism by which Xe induces anaesthesia, with little contribution of effects on GABAergic synapses. Key points: Xenon (Xe) non‐competitively inhibited whole‐cell excitatory glutamatergic current ( I Glu ) and whole‐cell currents gated by ionotropic glutamate receptors ( I AMPA, I KA, I NMDA ), but had no effect on inhibitory GABAergic whole‐cell current ( I GABA ). Xe decreased only the frequency of glutamatergic spontaneous and miniature excitatory postsynaptic currents and GABAergic spontaneous inhibitory postsynaptic currents without changing the amplitude or decay times of these synaptic responses. Xe decreased the amplitude of both the action potential‐evoked excitatory and the action potential‐evoked inhibitory postsynaptic currents (eEPSCs and eIPSCs, respectively) via a presynaptic inhibition in transmitter release. We conclude that the main site of action of Xe is presynaptic in both excitatory and inhibitory synapses, and that the Xe inhibition is much greater for eEPSCs than for eIPSCs.